Exploration and Enlightenment of Dual-system Vocational Education in Germany - Dong, Lingjiao (Journal of Theory and Practice in Education and Innovation, 2024)
Germany’s dual-system vocational education is well known in the world. In this paper, the dual system of vocational education organizations, enrollment, teaching, assessment and employment in-depth exploration, summed up its legal system is complete, active participation of enterprises, high social recognition, as well as vocational education teachers of high quality characteristics. And use this as a mirror to reflect on the localization of dual-system vocational education, and propose three ways to improve the teaching quality of vocational education.